2020
DOI: 10.21500/20112084.4190
|View full text |Cite
|
Sign up to set email alerts
|

Factorial Analysis and Invariance Testing for Age and Gender of the Reactive-Proactive Aggression Questionnaire (RPQ)

Abstract: Reactive aggression is characterized by high emotional activation, impulsivity, and hostility, while proactive aggression presents a cold, instrumental, and planned strategy. The aim was to perform a psychometric analysis of the Reactive-Proactive Aggression Questionnaire [RPQ]. A non-probability sample of 502 people between 18 and 40 years old was formed, grouped by sex (n=297, 59.2% women and n=205, 40.8% men) and age (n = 224, 44.62% under 25 years old and n=278, 55.38% over 25 years old). The instruments w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 38 publications
(70 reference statements)
0
4
0
Order By: Relevance
“…Descriptive statistics and correlation analysis were conducted using SPSS25.0. Previous studies have shown that age and gender may related to aggression or anger rumination ( Zsila et al, 2019 ; Toro-Tobar et al, 2020 ), therefore, age and gender were included in the correlation analysis. As predicted, analyses revealed significant relationships among all the studied variables (see Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Descriptive statistics and correlation analysis were conducted using SPSS25.0. Previous studies have shown that age and gender may related to aggression or anger rumination ( Zsila et al, 2019 ; Toro-Tobar et al, 2020 ), therefore, age and gender were included in the correlation analysis. As predicted, analyses revealed significant relationships among all the studied variables (see Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Notably, the links between CU traits and conduct problems at the daily within-person level could possibly be instantiated by their intermediate and differential links involving daily positive and negative affect. Although most research places negatively valenced emotion processes at the center of personality and psychopathology, some research has implicated positive affect in the development of aggressive behaviors (Toro et al, 2020 ). In addition, affect and emotion are best conceptualized as dynamic processes underpinning a range of psychopathological outcomes (Houben et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…64), which is thought to be attributable to high items loadings on both factors 11 . Nevertheless, factor analyses on the widely used Reactive-Proactive Questionnaire (RPQ) 12 support the two-factor structure of the functions of aggression [12][13][14] . Main forms of aggression include Physical Aggression (i.e., causing physical harm to others, e.g., hitting, biting, kicking, 15,16 ), Verbal Aggression (i.e., using speech to psychologically hurt others, e.g., shouting/screaming, insults, threats, 15,16 ), but also Indirect (i.e., relational, or social behaviors intended to harm social relationships, e.g., manipulation, damage relationships, 17,18 ).…”
Section: Introductionmentioning
confidence: 99%